MEMBRAN POLIURETAN DARI MINYAK BIJI KARET (RUBBER SEED OIL) DENGAN HEKSAMETILEN-1,6-DIISOSIANAT: SINTESIS - Salfauqi Nurman; Marlina Marlina; Saiful Saiful (Jurnal Natural, 2016)
Polyurethane membrane made from Rubber Seed Oil has been produced within this research. Rubber seed oil has the hydroxyl number of  40,33 mg/g  and the iodine number of  154,05 g/g which can be used as resource clusters; -OH, in order to make polyurethane. Rubber seed oil can react with hexamethylene-1.6-diisocyanate (HDMI) as another resource cluster, which is -NCO. The production of polyurethane membrane is done by variating the composition of rubber seed oil and HDMI, with the variations of 5:1; 5:3; 5:4; 5:5 dan 5:7 (v/w) and the polymrization temperature of 90-100°C and the curring temperature of  165-170°C. The optimal polyurethane membrane is produced on the composition of 5:4 v/w  which is homogenous, dry, quite elastic and is yellowish brown in colour. The IR results showed that there were urethan bonds formed (N-H on  ν = 3300-3400 cm-1) and the TGA results from polyurethane membrane showed that there were two decompositions on 394,5oC dan 458,6oC.